Identification of a Novel Peptide-based Medicine Derived from Boerhavia diffusa against β-lactamase TEM of Klebsiella pneumonia Using In silico Approaches - Ramarao, Venkatajothi; Periaswamy, Selvam; Selvam, Madhu Bala (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Klebsiella pneumoniae is the most prevalent pathogenic bacteria that cause nosocomial infections due to the expression of virulence factors and the emergence of drug resistance. β-lactamase could be the reason behind Klebsiella pneumoniae resistance to β-lactam drugs. In this study, we simulate the blaTEM protein sequence using In silico molecular docking techniques and integrate it into the novel peptide derived from Boerhavia diffusa. An automated drug docking server known as H-Dock server was used to ascertain how the peptide inhibits Klebsiella pneumonia multidrug resistance protein, blaTEM. The peptide and receptor combination was viewed using the advanced molecular visualization program Discovery Studio. The 3D interaction between the protein and the peptide demonstrated direct binding between the transmembrane regions and the functional domains. Thus, we conclude that the identified peptide is a new potential therapy for diseases associated with the multidrug-resistant protein blaTEM of Klebsiella pneumonia.